Prevalence of dental fear and its causes using three measurement scales among children in New Delhi - Anju Singh Rajwar; Mridula Goswami (Wolters Kluwer Medknow Publications, 2017)
Introduction: There is a great need for identifying fearful children, who often present problems in patient management, thus affecting the quality of dental care rendered to them. This study is unique in the way that dental fear was assessed through three fear scales as research has suggested the use of more than one scale because each scale has its own restrictions and is open to criticism. Aim: The aim of this study was to evaluate dental fear and anxiety (DFA) among children aged 3-14 years using three fear measurement scales. Methods: The study was conducted on children (3-14 years) who visited the Department of Pedodontics and Preventive Dentistry at Maulana Azad Institute of Dental Sciences, New Delhi. The DFA levels were measured using three fear measurement scales, i.e., facial image scale (FIS), dental fear scale (DFS), and children's fear survey schedule-dental subscale (CFSS-DS). The dental behavior was estimated using the Frankl's behavior rating scale (FBRS). Results: The prevalence of dental fear according to FIS was 14.3%, according to DFS was 22.6%, and according to CFSS-DS was 7.4%. In assessment of the behavior of children in the clinics through FBRS, it was observed that he maximum number of respondents (69.8%) showed Frankl's Rating 3 i.e. positive. In the DFS and CFSS-DS, the factor which caused most fear was "feeling the needle injected" and "injections," respectively. Conclusion: Assessment of dental fear is an extremely useful tool for the dental practitioner, who can use it to customize the behavioral treatment and management for child patients.